Edukasi Penyusunan Laporan Keuangan UMKM Pada Usaha Sokasi di Kabupaten Buleleng - Solikin, Akhmad; Marlina, Luh Sri; Dita Prabhayanti, Desak Putu (DHARMA BAKTI, 2022)
SMEs entrepreneurs could use gadget to promote their businesses, to communicate with consumers and suppliers, and to sale. In addition, the SMEs entrepreneurs could also utilize their gadgets to compile financial reports by using free applications available in the market. This article reports a community empowerment activity in order to help SMEs assemble financial report by using Akuntansi UKM application. A partner for the community empowerment activity is an entrepreneur of sokasi craft which is located in Buleleng District, Bali Province. For the education activity, a poster was created to help explain benefits and importance of financing reports, types of financial reports, and separation between private and business money. More detailed explanation for accounting processes is presented in a video which is then uploaded to social media.